Unique synergy for low velocity impact deformation reduction in Dyneema®-carbon intraply-interlayer hybrid composite panel - Zulkifli, Faiz (2023)
This work studies the synergies arising from the unique intraply-interlayer dual hybridization of unidirectional cross-ply Ultra-High Molecular Weight Polyethylene (UHMWPE) fiber ballistic panels with composite layers of woven mixed UHMWPE-Carbon (PE-C) on low velocity impact performance with focus on back face signature (BFS) changes. Force-displacements curves reveal the unique responses of these hybrid panels upon impact. Our results showed that a front or back-facing PE-C hybrid panel resulted in a substantial 26–29% reduction in BFS relative to the neat PE panel, whereas only a 19% and 10% reduction for the front and back C hybrid panel, respectively. The mixed PE-C composite layers proved to be superior when compared to homogeneous C composite layers in their ability to survive impact without catastrophic failure, thus more effectively contributing to the energy absorption and BFS reduction.